Confirmation of antiphospholipid antibody positivity: a year's results in a cohort of 113 patients - A. Ruffatti; E. Salvan; S. Olivieri; A. Bontadi; M. Tonello; T. Del Ross; S. Cuffaro; L. Punzi (PAGEPress Publications, 2011)
Objective: To evaluate the confirmation rate of antiphospholipid antibodies (aPL), to analyze their behaviour at confirmation time, and to study the clinical value of their confirmation. Methods: Blood samples from 380 subjects, enrolled in this study from June 1, 2007 to May 31, 2008, were tested for anti-cardiolipin (aCL) and anti-beta2glycoprotein (aβ2GPI) antibodies using an ELISA method and for Lupus anticoagulant (LA) using a series of clotting tests. The samples of the 113 subjects resulting positive at the first testing time were assayed again to confirm antiphospholipid positivity. Results: aPL positivity was confirmed in 67 out of the 113 subjects (59.3%). Medium-high antibody levels of all, except IgM aCL, aPL/ELISA had a significantly higher confirmation rate with respect to that in subjects with low levels. The confirmation rate in the category I antibody patients (multiple positivity) was higher than that in the category II antibody subjects (single positivity). LA positivity was confirmed only when it was associated to other aPL. The cut-off of 40 GPL produced a confirmation rate equal to that resulting from a 99th percentile cut-off. Confirmation of aPL positivity made it possible for us to confirm the diagnosis of antiphospholipid syndrome (APS) in 8 out of the 113 subjects originally resulting positive (7,1%). APS clinical features were vascular thrombosis in 4 of these and pregnancy morbidity in the other 4. Conclusions: Our data emphasize aPL positivity confirmation selectivity, and medium-high antibody levels and category I antibodies (multiple positivity) had the best confirmation rates.